2016
DOI: 10.1073/pnas.1521827113
|View full text |Cite
|
Sign up to set email alerts
|

High-throughput small molecule screen identifies inhibitors of aberrant chromatin accessibility

Abstract: Mutations in chromatin-modifying proteins and transcription factors are commonly associated with a wide variety of cancers. Through gain-or loss-of-function, these mutations may result in characteristic alterations of accessible chromatin, indicative of shifts in the landscape of regulatory elements genome-wide. The identification of compounds that reverse a specific chromatin signature could lead to chemical probes or potential therapies. To explore whether chromatin accessibility could serve as a platform fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 56 publications
(48 reference statements)
3
22
0
Order By: Relevance
“…As such, epigenetic therapy has been considered as an attractive treatment strategy in ES. Pattenden et al [35] previously identified that a cluster of HDAC inhibitors including entinostat significantly decreased EWS-FLI1-dependent chromatin accessibility by decreasing EWS-FLI1 levels, which explained our predictions in in silico screen that entinostat can reverse the ES disease signature and EWS-FLI1-mediated transcriptional signature. Besides entinostat, other HDAC inhibitors (e.g., romidepsin, vorinostat, sodium butyrate) have also shown potent anti-ES activity [22,36,37], which provides convincing evidence of the epigenome as a therapeutic target in ES.…”
Section: Discussionsupporting
confidence: 75%
“…As such, epigenetic therapy has been considered as an attractive treatment strategy in ES. Pattenden et al [35] previously identified that a cluster of HDAC inhibitors including entinostat significantly decreased EWS-FLI1-dependent chromatin accessibility by decreasing EWS-FLI1 levels, which explained our predictions in in silico screen that entinostat can reverse the ES disease signature and EWS-FLI1-mediated transcriptional signature. Besides entinostat, other HDAC inhibitors (e.g., romidepsin, vorinostat, sodium butyrate) have also shown potent anti-ES activity [22,36,37], which provides convincing evidence of the epigenome as a therapeutic target in ES.…”
Section: Discussionsupporting
confidence: 75%
“…FAIRE relies on differential crosslinking efficiency between DNA bound by nucleosomes versus DNA in nucleosome-depleted regions, where an increase in FAIRE signal indicates a reduction in nucleosome density [ 33 – 35 ]. As a control, we probed the FAIRE signal at AURKAIP1, a region of host chromatin that is consistently nucleosome depleted [ 36 ]. Romidepsin and Panobinostat treatment resulted in a 1.9- to 5.9-fold increase in the FAIRE signal at four regions of the RTA promoter compared to DMSO treated cells ( Fig 6A ).…”
Section: Resultsmentioning
confidence: 99%
“…A number of different pharmacologic manipulations have been shown to alter EWS/Fli1 oncofusion levels in Ewing Sarcoma [ 37 – 39 ]. Since the oncofusion is known to promote cell proliferation and survival [ 40 ], downregulation of EWS/Fli1 levels could account for the observed opposing effects of JIB-04 on the EWS/Fli1-controlled transcriptome.…”
Section: Resultsmentioning
confidence: 99%